1999
DOI: 10.1021/bi982497j
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure Determination of Cholesterol Oxidase from Streptomyces and Structural Characterization of Key Active Site Mutants,

Abstract: Cholesterol oxidase is a monomeric flavoenzyme which catalyzes the oxidation and isomerization of cholesterol to cholest-4-en-3-one. The enzyme interacts with lipid bilayers in order to bind its steroid substrate. The X-ray structure of the enzyme from Brevibacterium sterolicum revealed two loops, comprising residues 78-87 and residues 433-436, which act as a lid over the active site and facilitate binding of the substrate [Vrielink et al. (1991) J. Mol. Biol. 219, 533-554; Li et al. (1993) Biochemistry 32, 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
136
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(140 citation statements)
references
References 28 publications
4
136
0
Order By: Relevance
“…In BCO1 structural (6,29) and mutagenesis and kinetic studies (30) have indicated that a single glutamate residue (Glu 361 ) functions as the acid/base in proton abstraction from C-4 and reprotonation at C-6 of the steroid. The steroid bound model for BCO2 also reveals a glutamate (Glu 475 ) near to the isomerization center.…”
Section: Resultsmentioning
confidence: 99%
“…In BCO1 structural (6,29) and mutagenesis and kinetic studies (30) have indicated that a single glutamate residue (Glu 361 ) functions as the acid/base in proton abstraction from C-4 and reprotonation at C-6 of the steroid. The steroid bound model for BCO2 also reveals a glutamate (Glu 475 ) near to the isomerization center.…”
Section: Resultsmentioning
confidence: 99%
“…To illustrate, His-447 abstracts the C3-hydroxyl proton of cholesterol in cholesterol oxidase (30). It is possible that His-233 in GlpD can perform this function on the hydroxyl proton of C2 in G3P although at 4.7 Å, this mechanism is less probable.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that H2O2 has a key role in aging [4]. Furthermore, it is formed as a by-product in various enzymatic reactions, such as those catalyzed by glucose oxidase [5], glutamate oxidase [6], and cholesterol oxidase [7]. Enzymatic production makes H2O2 feasible for biosensor applications as it typically has lower oxidation potential compared to the enzyme substrate molecules.…”
Section: Introductionmentioning
confidence: 99%